Impact of sublethal zinc exposure on ectomycorrhizal Laccaria bicolor x poplar symbiosis - Ottaway, Maarten; Swinnen, Janne; Verhaevert, Katoo; Ruytinx, Joske (Frontiers in Plant Science, 2025)
Soil Zn pollution is a widespread problem that is impacting on plant growth and production. Several tree species can rely on fungal ectomycorrhizal symbionts to mitigate toxicity effects to some extent. Here, we explored the impact of Zn pollution on L. bicolor and its ectomycorrhizal symbiosis with Populus tremula x alba. Next to growth and morphological parameters in sublethal Zn exposure, we investigated responses of symbiosis marker genes, reactive oxygen species scavenging enzymes and Zn transporters in presence and absence of a host plant. Our results indicate that the ECM symbiosis development is maintained in excess Zn conditions despite a reduction in fungal and plant growth. Symbiosis marker gene expression showed sensitivity to Zn excess, even when the fungus was cultured in absence of a host. Zn-induced transcriptional responses of ROS scavenging enzymes and Zn transporters were mainly restricted to mycelia in presence of a host and less prevalent without host. Establishment of new homeostatic equilibria, in particular in presence of a host, seem essential to maintain symbiosis, protect the host and adapt physiologically to Zn pollution. This research furthers our understanding of how resilient plant-fungal symbiotic interactions are, and the interplay between both partners in changing environmental conditions.